Niger - Integrated State-Owned Enterprise Framework iSOEF - World Bank (Washington, DC: World Bank, 2022)
This Integrated State-Owned Enterprises Framework (iSOEF) assessment has been carried out in the context of the World Bank’s dialogue with the government of Niger (GoN) on state-owned enterprises (SOEs). The GoN is considering progressive reform to control SOE-related budget expenditures, improve financial and operational performance, and better manage emanating fiscal risks. The Niger iSOEF focuses on the fiscal implications of SOE reform and on corporate governance and accountability mechanisms. Based on the fiscal risk assessment and diagnosis of governance rules and practices, this study incorporates an action plan of policies and options for reforms that are deemed feasible within Niger’s context.The report is organized as follows. Chapter 2, the SOE Landscape, provides an overview of the SOE sector in Niger, covering the size, scope, and performance of SOEs. Chapter 3, based on Module 2 of the iSOEF, provides a fiscal risk assessment of the SOE sector, including a fiscal sustainability analysis covering different scenarios. Chapter 4, based on Module 4 of the iSOEF, reviews the corporate governance and accountability mechanisms pertaining to SOEs in Niger, including the legal and regulatory framework and the state’s oversight role and capacity to exercise its ownership and control functions effectively. Chapter 5 proposes reform options, adapted to the country context, that target improved SOE governance in the short and medium term.